2019
DOI: 10.4149/gpb_2019037
|View full text |Cite
|
Sign up to set email alerts
|

circCDYL/microRNA-150-5p participates in modulating growth and migration of colon cancer cells

Abstract: Circular RNA-microRNA (circRNA-miR) node has recently been found to modulate cancer process. Here, we investigated whether circCDYL and miR-150-5p exerted biological function in colon cancer cells. Colon cancer tissues were collected and subjected to qRT-PCR assay for circCDYL and miR-150-5p. SW480 and SW620 cells were forced to overexpress circCDYL and miR-150-5p before subjected to viability, colony formation, apoptosis, migration, invasion and protein (associated with proliferation, apoptosis and signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…For example, ectopic hsa_circ_0026782 (circITGA7) expression inhibits the growth and metastasis of CRC cells in vitro and in vivo, whereas the knockdown of circITGA7 promotes the proliferation and migration of CRC cells in vitro and increases CRC growth in vivo [89,90]. Moreover, hsa_circ_0008285 (circCDYL) decreases cell viability, impairs migration and invasion behaviors, and promotes cell apoptosis in CRC [91,92]; hsa_circ_ 0026344 overexpression decreases the growth and invasion of CRC cells while inducing cell apoptosis in vitro and inhibiting CRC growth in vivo [93,94]. In addition, some circRNAs inhibit the epithelial-mesenchymal transition (EMT), which is a process strongly correlated with metastasis, in CRC cells [73,94,95] (Fig.…”
Section: Oncogenic Functionsmentioning
confidence: 99%
“…For example, ectopic hsa_circ_0026782 (circITGA7) expression inhibits the growth and metastasis of CRC cells in vitro and in vivo, whereas the knockdown of circITGA7 promotes the proliferation and migration of CRC cells in vitro and increases CRC growth in vivo [89,90]. Moreover, hsa_circ_0008285 (circCDYL) decreases cell viability, impairs migration and invasion behaviors, and promotes cell apoptosis in CRC [91,92]; hsa_circ_ 0026344 overexpression decreases the growth and invasion of CRC cells while inducing cell apoptosis in vitro and inhibiting CRC growth in vivo [93,94]. In addition, some circRNAs inhibit the epithelial-mesenchymal transition (EMT), which is a process strongly correlated with metastasis, in CRC cells [73,94,95] (Fig.…”
Section: Oncogenic Functionsmentioning
confidence: 99%
“…It has been reported that circRNAs may mediate upregulation or downregulation of gene expression and, despite being classified as noncoding, may also encode proteins [13]. Moreover, circRNAs are stable and widely expressed in many tumor tissues [14,15]. Some circRNAs have important biological functions and can be considered as biomarkers for diagnosis of multiple diseases [4,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Through their miRNA-sponging action ( Figure 3 A), several circRNAs regulate the proliferation and migration of CRC cells and affect therapy resistance. For instance, circ-CDYL has been shown to bind to miR-150-5p, the upregulation of which has been associated with the downregulation of PTEN and phosphorylation of PI3K, AKT, JAK2, and STAT5, which are key players in CRC signaling [ 32 ].…”
Section: Functions In Crcmentioning
confidence: 99%